Endoscopic Endonasal Dacryocystorhiniostomy (EEDCR) (Libyan Experience) - Tuhami, Mr.Masoud; Elbargathy, Dr.Halima; A Belkhair, Dr.Hussain; Elfleleh, Mr.Salem; Gaber, Dr.‎Salah; Omae, ‎Mr.Salem (Libyan Journal of Dentistry, 2020)
Endoscopic endonasal dacryocystorhiniostomy (EEDCR) is a valid alternative to external procedures in the management of nasolacrimal duct obstruction with success rate ranging from 82% to 95% . It is a less invasive procedure, can be done both under general and local anesthesia Patients and methods: In the present study twenty patients (18 Females and 2 males), aged 17 to 65 years were studied in the period between May 2009 to March 2010 to determine the success rate of such operations. All cases were operated under general anesthesia with the help of zero endoscope and drill of lacrymal bone. Results: Stents were applied in 5 recurrent cases after failed external approach, unresolved acute dacryocystites with abscess formation, and dacryocystocele. Few complications were encountered (such as granulation tissue at operative site in 4 cases, recurrence of symptoms due to incomplete removal of mucosal flap, and synechia between lateral nasal wall and middle turbinate). Conclusion: After a follow up of 6 months the success rate in this series was 95%. Thus it is suggested that stent application should not be carried out routinely in every case, while close and regular follow up helps early identification of complications, early intervention and hence it decreases the recurrence and revision surgery.